Reasons for medication errors in nurses’ veiws - Nikpeyma, N; Gholamnejad, H (Advances in Nursing & Midwifery, 2009)
Background Medication error in nursing is one of the most common errors of healthcare systems (over 78%) with detrimental outcomes. Different reasons have been suggested in this regard and it seems that further investigations are still needed. Purpose This descriptive study was conducted to identify the reasons for medication errors in nurses’ views. Methods 100 nurses from different wards at several hospitals completed a 3-part questionnaire including demographic, occupational and medication error questions. Content and test-retest methods were used for validity and reliability of the questionnaire respectively. Different tests were used for statistical analysis of data. Results 53% of the subjects reported medication errors at least 1 time in their work experience. The most common ones were wrong dose (27%), drug neglect (22%) and wrong time (18%) respectively. Most errors were made by nurses between 25 and 30 (51%), at neonatal and pediatric wards (60%) and mainly in morning shifts (65%). The most common reasons included heavy workload (70%), shortage of staff (62%), physical and emotional fatigue (59%) and lengthy working hours (58%). Conclusion It can be concluded that the 3 reasons for making errors refer to organizational-humanistic factors. In fact, insufficiency in healthcare system leads to increased medication errors. Identification of these factors can help both healthcare system and nurses to eliminate them and decrease the errors resulting in improved quality care and patient’s safety. Keywords: Medication errors, Nurses, Reasons.